2012
DOI: 10.1073/pnas.1205532110
|View full text |Cite
|
Sign up to set email alerts
|

Accurate prediction of secondary metabolite gene clusters in filamentous fungi

Abstract: Biosynthetic pathways of secondary metabolites from fungi are currently subject to an intense effort to elucidate the genetic basis for these compounds due to their large potential within pharmaceutics and synthetic biochemistry. The preferred method is methodical gene deletions to identify supporting enzymes for key synthases one cluster at a time. In this study, we design and apply a DNA expression array for Aspergillus nidulans in combination with legacy data to form a comprehensive gene expression compendi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
189
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 213 publications
(197 citation statements)
references
References 56 publications
7
189
0
1
Order By: Relevance
“…A method to predict secondary metabolite gene clusters in filamentous fungi has recently been devised. 8 Interestingly, microbial production of secondary metabolites is limited to a very low level by certain regulatory mechanisms. Despite this, the extent of such production is sufficient for the microbe to compete with other organisms or maintain a commensal/mutual relationship with other species.…”
Section: Introductionmentioning
confidence: 99%
“…A method to predict secondary metabolite gene clusters in filamentous fungi has recently been devised. 8 Interestingly, microbial production of secondary metabolites is limited to a very low level by certain regulatory mechanisms. Despite this, the extent of such production is sufficient for the microbe to compete with other organisms or maintain a commensal/mutual relationship with other species.…”
Section: Introductionmentioning
confidence: 99%
“…Culture in liquid and solid media affected SM gene expression, which is often found during the production of other SM (Andersen et al, 2013), and the present findings indicated that A. nidulans SirA discriminates culture conditions upon expression of the AUS/ DAUS synthetic genes. An increase in cellular NAD + , which is a substrate for sirtuin-dependent histone deacetylation, stimulates the activity of mammalian and yeast sirtuins (Haigis and Guarente, 2006;Kato and Lin, 2014).…”
Section: Sira Represses Gene Clusters Associated With Secondary Metabmentioning
confidence: 68%
“…The latter contained 32 genes associated with the production of the secondary metabolites used for synthesizing SM, such as ST, PN, xanthone and shamixanthone (XPT), the fungal siderophore (SID), emericellamide (EAS), austinol and dehydroaustinol (AUS/DAUS), aspernidine A (ASP), cichorine (CIC), ent-pimara-8(14),15-diene (EPD) (Andersen et al, 2013), the aromatic amino acid, fumiquinazoline C, ergot alkaloid and an unknown polyketide (Table S2). Other genes in Set 2 were assigned to a "monodictyphenone (MDP) metabolic process" (P < 1 ¥ 10 -5 ), and a "MDP biosynthetic process" (P < 1 ¥ pounds migrating at 12.6 min were m /z = 457.…”
Section: Sira Represses Gene Clusters Associated With Secondary Metabmentioning
confidence: 99%
“…In addition, a select group of these compounds have been developed in the clinic with important applications such as antibiotics, immunosuppressors, and other chemotherapeutic agents. Microbial genome mining efforts to explore fungal biosynthetic potential have shown that the fungal secondary metabolome has been substantially underestimated and that a large majority of fungal secondary metabolite biosynthetic gene clusters may remain silent under laboratory cultivation conditions [1,2].…”
Section: Introductionmentioning
confidence: 99%